Analysis on contamination status and dietary exposure assessment of fumonisins in cereal and oil food samples of a coastal city in northern China - Dong, Fengguang; Feng, Xueying; Zhang, Yiyi; Gong, Chunbo; Chen, Youxia; Huo, Yapeng; Yan, Xige; Wang, Guiqiang (Food Science and Technology, 2023)
Fumonisin is a class 2B carcinogen, which can pollute many food varieties and has been proved to be carcinogenic and teratogenic. 258 pieces cereal and oil food samples were collected from 14 districts in Yantai city from farmers' homes, supermarkets and farmers' markets. The contamination level of fumonisins was detected by High-performance liquid chromatography-tandem mass spectrometry. The pollution level of fumonisin was determined by CODEX STAN 193-1995 and EC No 1881/2006. We conducted quantitative risk assessment of fumonisins through the Daily intake (EDI) and Hazard Quotient (HQ) by point assessment method. Corn and its products were multiple polluted by FBs, and the pollution degree of corn flour and corn-based cake were higher than that of corn kernels. The food exposure risk of FBs in 2-6 years old was higher than that of standard population, urban standard population and rural standard population. The exposure risk of fumonisins in high consumption group was higher than that in general consumption group. The food exposure risk of corn with average content of fumonisins was basically at an acceptable level, but corn and its products with high FBs content caused greater risk for children aged 2-6 years old and adults with high corn consumption.